Using the Five-Level Taiwan Triage and Acuity Scale Computerized System: Factors in Decision Making by Emergency Department Triage Nurses. (October 2017) - Chang, Wen; Liu, Hsueh-Erh; Goopy, Suzanne; Chen, Li-Chin; Chen, Hsiao-Jung; Han, Chin-Yen
Triage classifies and prioritizes patients' care based on the acuity of the illness in emergency departments (EDs). In Taiwan, the five-level Taiwan Triage and Acuity Scale (TTAS) computerized system was implemented nationally in 2010. The purpose of this study was to understand which factors affect decision-making practices of triage nurses in the light of the implementation of the new TTAS tool and computerized system. The qualitative data were collected by in-depth interviews. Data saturation was reached with 16 participants. Content analysis was used. The results demonstrated that the factors affecting nurses' decision making in the light of the newly implemented computerized system sit within three main categories: external environmental, patients' health status, and nurses' experiences. This study suggests ensuring the patient's privacy while attending the triage desk, improving the critical thinking of triage nurses, and strengthening the public's understanding of the ED visits. These will make ED triage more efficient.